1986
DOI: 10.1017/s0001566000006309
|View full text |Cite
|
Sign up to set email alerts
|

Monoamniotic Twin Pregnancy

Abstract: The course and outcome of 23 monoamniotic (MA) twin pregnancies, delivered in Tampere University Central Hospital during the years 1964-1984, were studied retrospectively and compared to 1056 diamniotic (DA) twin pregnancies. The frequency of MA twins was 2.1% of twin pregnancies. Polyhydramnion complicated the pregnancy in 26% of MA vs 6% of DA pregnancies. Two cases were defined as acute polyhydramnion. Preterm labour was stated in 70% of MA pregnancies and deliveries before the 34th week were 4 times more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Perinatal mortality was reported to be 28-47% and 32% by Lumme and Saarikoski, and Demaria et al, respectively 3, 4. This high mortality was known to be caused by prematurity, twin to twin transfusion syndrome, congenital anomalies, intrauterine growth restriction, and umbilical cord entanglement 5, 6.…”
Section: Discussionmentioning
confidence: 98%
“…Perinatal mortality was reported to be 28-47% and 32% by Lumme and Saarikoski, and Demaria et al, respectively 3, 4. This high mortality was known to be caused by prematurity, twin to twin transfusion syndrome, congenital anomalies, intrauterine growth restriction, and umbilical cord entanglement 5, 6.…”
Section: Discussionmentioning
confidence: 98%
“…Although uncommon, monoamniotic twins are associated with high antenatal and perinatal mortality. In 1986, Lumme et al reported a perinatal mortality rate of 28-47% (2). However, in the article by Allen et al (3), the perinatal mortality was 10% of all babies in their case series and 12.5% in the literature review.…”
Section: Complicationsmentioning
confidence: 96%
“…In 1986, Lumme et al. reported a perinatal mortality rate of 28–47% (2). However, in the article by Allen et al.…”
Section: Complicationsmentioning
confidence: 99%
“…In addition, twintwin transfusion syndrome is a common cause of fetal death in monoamniotic twin gestations [5]. In the current case, no superficial vessel anastomosis was recognized in the placenta.…”
Section: Discussionmentioning
confidence: 51%